The Effect of Islamic Service Quality on Repurchase Intention Through Customer Satisfaction: Study at Musa’adah Kopontren Retail Sukorejo Situ-bondo - Abi Kusairi; Raden Andi Sularso; Mochammad Farid Afandi (Harmony Management: International Journal of Management Science and Business, 2026)
This study aims to examine the effect of Islamic Service Quality comprising compliance, assurance, reliability, tangibles, empathy, and responsiveness on repurchase intention through consumer satisfaction at the Musa’adah Kopontren Retail, Sukorejo Situbondo. This research employs an explanatory research design. The sampling technique used is non-probability sampling with a purposive sampling method. Data were collected a questionnaire distributed both directly and via Google Forms, involving a total of 240 respondents. The data analysis method applied is Partial Least Squares (PLS) using SmartPLS software. The results indicate that: (1) compliance has a significant effect on consumer satisfaction; (2) assurance has a significant effect on consumer satisfaction; (3) reliability has no significant effect on consumer satisfaction; (4) tangibles have a significant effect on consumer satisfaction; (5) empathy has a significant effect on consumer satisfaction; (6) responsiveness has a significant effect on consumer satisfaction; (7) compliance has no significant effect on repurchase intention; (8) assurance has no significant effect on repurchase intention; (9) reliability has no significant effect on repurchase intention; (10) tangibles have a significant effect on repurchase intention; (11) empathy has no significant effect on repurchase intention; (12) responsiveness has no significant effect on repurchase intention; and (13) consumer satisfaction has a significant effect on repurchase intention.